2009
DOI: 10.1159/000242998
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Equivalence of Controlled-Release Oxycodone 20 mg and Controlled-Release Tramadol 200 mg after Surgery for Breast Cancer

Abstract: Aims: To assess clinical equivalence of 20 mg controlled-release oxycodone (Oxygesic®; Mundipharma, Limburg, Germany) and 200 mg controlled-release tramadol (Tramal long®; Grünenthal, Aachen, Germany) on a 12-hour dosing schedule in a randomized, double-blinded study of 54 ASA I–III physical status (American Society of Anesthesiologists classification of physical status) patients undergoing surgery for breast cancer. Methods: General anesthesia using remifentanil and propofol was performed for surgery. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…The rates of patient satisfaction on the overall perception of the treatment of postoperative pain found in the study by Kampe et al 22 is similar to the opinion of the investigator on the treatment used in this study.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 86%
“…The rates of patient satisfaction on the overall perception of the treatment of postoperative pain found in the study by Kampe et al 22 is similar to the opinion of the investigator on the treatment used in this study.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 86%
“…In a dosing survey study of CRO for chronic pain, Marcus et al (23) reported the effective dosage of CRO as 60-120 mg daily. The majority of studies on pain relief suggested that doses of 10-30 mg twice daily are sufficient for management of variable pain (13,16,25). In our study, we compared doses of 20 and 10 mg of CRO, and the results were mixed.…”
Section: Efficacy Assessmentmentioning
confidence: 88%
“…The occurrence of PONV associated with oral oxycodone was comparable to that of placebo (laparoscopic cholecystectomy [23], gynecological laparoscopic surgery [24], and breast surgery [22]), intravenous piritramide (caesarean section [39]), oral tramadol (breast surgery [37]) and naproxen (knee arthroscopy or inguinal hernia repair surgery [31]).…”
Section: Postoperative Side Effectsmentioning
confidence: 91%
“…Patient satisfaction with postsurgical analgesia was generally high and comparable between treatments in most of the trials (22,24,25,31,37,39). However, the quality of pain management for oxycodone treatment was rated higher by patients undergoing spine surgery (versus placebo) (21) and retinal surgery (versus tramadol) (43), as was the quality of pain management for a multimodal regimen involving oxycodone in the setting of knee arthroplasty (versus intravenous hydromorphone) (30) and spine surgery (versus intravenous morphine or hydromorphone) (36).…”
Section: Satisfactionmentioning
confidence: 91%
See 1 more Smart Citation